Experiment and Analysis of Cord Stress on High-Speed Radial Tire Standing Waves. (30th July 2019) - Sun, Peng-Fei; Huang, Hong-Wu; Zhou, Shui-Ting; Chiu, Yi-Jui; Du, Meng; Zhao, Dong-Hao
Abstract : This paper elaborates on the production mechanisms of standing waves during high-speed tire rolling and analyzes the relationship between the change of wavelength of sidewall waves and the vehicle velocity, from an oblique wave point of view. A finite element model for a 195/65R15 radial tire is established with the nonlinear analysis software ABAQUS, based on the tire structure and cord parameters. This paper comparatively analyzes the finite element simulation results and experimental results of the tire load-sinkage relation and the load vs inflatable section width relation and finds little difference between the simulation and experimental results. A similar analysis studies the change in the wavelength of sidewall standing waves at different vehicle velocities during high-speed tire rolling. The calculated value by the oblique wave approach, the value by simulation, and the experimental results demonstrate high consistency, concluding that during high-speed tire rolling, the wavelength of sidewall standing waves increases with vehicle velocity. Thus, the accuracy of the finite element model is verified under both static and dynamic conditions. Under a constant tire pressure and load, the impact of velocity change on tire-cord stress during high-speed tire rolling is studied based on the finite element model so as to identity the relation between the cord stress and standing waves.